(3TQM GdJHUQIs - (3Gdbej GdMGFQj, Gdbej, MSf Hf ESeGYjd GdMSjfj Gdbej, cGf MkjG (B1304(3g` (B1887(3es ((3GdeOQSI GdRjfHjI HcQHdGAs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg QH GdYGdejf (B... (3cJGH GdUhe GdPj CMO CQcGf GdESdGe heG Hfj Ydjg aVdG Yf chfg CMO hGLHGJg ddYdhe hLhHg HVQhQI GdQTY hELeGY Cgdgs
(3BNQgG (B:s
(3BNQgG(B: (3aj GdOQhS Cfg XGgQ GdePgH (B... (3GdeYQha LedI ef GdcJH hdYeQj Ef eSFdI GdbVGA Yf GdejJ (B... (3hdeG cGf aj bUOj GdTQhY hEJeGe GdcdGe ajgG GNJUQJ aj GdebGes
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf, L (B1: 539s
(3GdPQjYI, L (B13: 82s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis